Overweight and obesity in children and adolescents with endocrine disorders - Pomahacova, Renata; Paterova, Petra; Nykodymova, Eva; Polak, Petr; Sladkova, Eva; Skalicka, Eva; Sykora, Josef (Biomedical papers, 2023)
Obesity has become a serious medical condition where many factors can contribute to excess weight gain. The most common type of childhood obesity is simple obesity, which is due to gene-obesogenic environment interaction. Only a minority are due to pathological causes. Secondary causes of obesity, while less common, include these: genetic syndromes, drug-related obesity, as well as endocrine disorders (hypothyroidism, Cushing's syndrome, growth hormone deficiency, hypogonadism, pseudohypoparathyroidism type Ia, insulinoma, hypothalamic obesity and polycystic ovary syndrome). Given that some conditions may be treatable, physicians must be aware of obesity due to endocrinopathies and distinguish them from simple obesity, and treat them properly. Although rare among children, early detection of the endocrine cause of obesity leads to reduced morbidity and, in some cases, reduced mortality in these individuals. The aim of this review is to summarize the current findings on obesity-related endocrinopathies in children (illustrated by clinical examples), highlighting aspects of pathogenetic mechanisms, genetics, the clinical diagnosis, growth, body mass index and possible therapeutic approaches. Early detection and correction of endocrine obesity is of paramount importance for obese children who could benefit from timely diagnosis and an improved management of obesity as many disturbances related to obesity can be reversed at the early stage, if weight loss is achieved.
Keywords: secondary obesity; hypothyroidism; growth hormone deficiency; Cushing's syndrome; hypogonadism; pseudohypoparathyroidism type Ia; insulinoma; hypothalamic obesity; polycystic ovary syndrome